Catherine : the great journey - Gregory, Kristiana (Royal diaries., 2005)
A fictional diary of Princess Sophie, later named Catherine, from 1743 until 1745, when at age fifteen she is married to her second cousin Peter, Grand Duke of Russia, who will one day be Emperor. Includes historical notes on her later life.